PENGARUH PENDIDIKAN KATOLIK TERHADAP PERKEMBANGAN KARAKTER SISWA-SISWI NON-KATOLIK DI SDK ST. YOSEPH 3 NAIKOTEN II KUPANG - Keraf, Oswaldus Agustinus Kerobi; Dau, Yoseph Lodowik Deki (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2021)
The purpose of the study was: (1) to find out how the situation of Catholic Education and the Character of Non-Catholic Students in SDK St. Joseph 3 Naikoten II Kupang and (2) to find out whether Catholic Education has a positive and significant effect on the character of Non-Catholic Students in the SDK St. Joseph 3 Naikoten II Kupang. The research method used is quantitatively deductive. The study population was non-Catholic students of class IV-VI SDK which amounted to 41 people. Using saturated sampling techniques, researchers focused on 41 respondents. The results of descriptive statistical analysis showed that the Catholic Education variable with 18 statement items obtained a total answer value of respondents to Non-Catholic students in grade IV-VI, which was 83% in the good category and the Character variable of Non-Catholic Students with 22 items of total statement of respondent's answer value of 84% was in a good category. A simple linear regression test obtained the variable coefficient value of Catholic Education (X) of 1,162 and the value (Sig) of The Catholic Education Variable of 0.000 so that it was concluded that Catholic Education has a positive and significant influence on the character of Non-Catholic students.